PERANAN PPAT PADA PEMBEBANAN HAK TANGGUNGAN DALAM PROSES PEMBERIAN KREDIT MENURUT UNDANG-UNDANG NOMOR 4 TAHUN 1996 - Aji M Seprio Prandana (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTION     The purpose of this research is to know clearly how the role of PPAT in its lending process pursuant to Law No. 4 of 1996 and as well as knowing the constraints faced by the PPA officials in a process of giving a creditor against the debtor.This research is descriptive research and also includes normative and empirical research. The research location is in the Notary's office-PPAT Aji suryana JJ, SH., Samarinda. The type of data used are primary data sourced from Notary-PPAT, Mr AJi suryana JJ, SH., Directly on PPAT secondary data derived from the library as well as regulations relating to the title of the thesis. Data collection techniques used is to conduct interviews directly and compared to the regulations of the Act. Analysis of the data used is qualitative analysis to understand and assemble the data that have been obtained and arranged systematically, then conclude. Based on the research that I did, it could be concluded that PPAT is very important in an active role in the credit process and granting rights to the imposition of the debtor, in Article 15 paragraph (1) of the Act Encumbrance explained that SKMHT (Power of Attorney Mebebankan Encumbrance) shall be made by deed of Notary and PPAT deed. There are also objects that can be pledged as a receivable as objects Property Rights, Right to building, Right to Use, leasehold. PPAT also there are various kinds kendalai in its implementation. Some legal consequences because Imposition Encumbrance such as reduced management rights on authorizer, and entitlements preferred (preferred) to the Holder Mortgage, Encumbrance Certificates have executorial Tittle. Keywords: PPAT, Mortgage, Loan Process, Law No. 4 of 1996.